Sex Disparities in Access to Acute Stroke Care: Can Telemedicine Mitigate this Effect? - Wolff, Catherine (J Health Dispar Res Pract, 2016)
BACKGROUND: Women have more frequent and severe ischemic strokes than men, and are less likely to receive treatment for acute stroke. Primary stroke centers (PSCs) have been shown to utilize treatment more frequently. Further, as telemedicine (TM) has expanded access to acute stroke care we sought to investigate the association between PSC, TM and access to acute stroke care in the state of Texas. METHODS: Texas hospitals and resources were identified from the 2009 American Hospital Association Annual Survey. Hospitals were categorized as: (1) stand-alone PSCs not using telemedicine for acute stroke care, (2) PSCs using telemedicine for acute stroke care (PSC-TM), (3) non-PSC hospitals using telemedicine for acute stroke care, or (4) non-PSC hospitals not using telemedicine for acute stroke care. The proportion of the population who could reach a PSC within 60 minutes was determined for stand-alone PSCs, PSC-TM, and non-PSCs using TM for stroke care. RESULTS: Overall, women were as likely to have 60-minute access to a PSC or PSC-TM as their male counterparts (POR 1.02, 95% CI 1.02-1.03). Women were also just as likely to have access to acute stroke care via PSC or PSC-TM or TM as men (POR 1.03, 95% CI 1.02-1.04). DISCUSSION: Our study found no sex disparities in access to stand alone PSCs or to hospitals using TM in the state of Texas. The results of this study suggest that telemedicine can be used as part of an inclusive strategy to improve access to care equally for men and women.